Knowledge, Attitude and Practice Regarding Prophylactic Use of Antibiotics Among Crri Students in A Private Dental Institution -A Questionnaire Based Study - G, NIVETHA; D, SRI SAKTHI; S, ARVIND (The journal of contemporary issues in business and government, 2021)
Antibiotics are important in the management and prophylaxis of infection in patients at risk experiencing microbial disease.Overuse and inappropriate use of antibiotics is closely related to an increase in bacterial resistance.The aim of this present study is to assess the knowledge, attitude,practice of interns who are studying in Saveetha Dental College regarding prophylactic use of antibiotics.A cross sectional study was carried in April 2020 among interns of Saveetha Dental College and Hospital,Chennai.A questionnaire based study .A questionnaire consisting of 15 questions on knowledge ,attitude and practice regarding prophylactic use of antibiotics were formulated and distributed among interns through Google forms.The responses were obtained and entered in Excel sheet.A chi square test were done between gender and knowledge,gender and attitude and gender and practice using SPSS software.The independent variables were age and gender while dependent variables were knowledge,attitude and practice of prophylactic use of antibiotics.The results showed that about 52.89% of interns had fair knowledge, 51.92% had negative attitude,44.23% had good practice towards prophylactic use of antibiotics The present study concludes that interns possessed fair knowledge but a negative attitude and moderate practice on prophylactic use of antibiotics.